Broad Environmental Tolerance for a Salicola Host-Phage Pair Isolated from the Cargill Solar Saltworks, Newark, CA, USA - Meghan L. Rodela; Shereen Sabet; Allison Peterson; Jesse G. Dillon (Microorganisms, 2019)
Phages greatly influence the ecology and evolution of their bacterial hosts; however, compared to hosts, a relatively low number of phages, especially halophilic phages, have been studied. This study describes a comparative investigation of physicochemical tolerance between a strain of the halophilic bacterium, Salicola, isolated from the Cargill Saltworks (Newark, CA, USA) and its associated phage. The host grew in media between pH 6–8.5, had a salinity growth optimum of 20% total salts (ranging from 10%–30%) and an upper temperature growth limit of 48 °C. The host utilized 61 of 190 substrates tested using BIOLOG Phenotype MicroArrays. The CGφ29 phage, one of only four reported Salicola phages, is a DNA virus of the Siphoviridae family. Overall, the phage tolerated a broader range of environmental conditions than its host (salinity 0–30% total salts; pH 3–9; upper thermal limit 80 °C) and is the most thermotolerant halophilic phage ever reported. This study is the most comprehensive investigation to date of a Salicola host–phage pair and provides novel insights into extreme environmental tolerances among bacteriophages.